Engineering phase and polarization singularity sheets - Lim, Soon Wei Daniel; Park, Joon-Suh; Meretska, Maryna L.; Dorrah, Ahmed H.; Capasso, Federico (Nature Publishing Group, 2021)
Metasurfaces allow for vast possibilities of light control. Here, the authors demonstrate on-demand engineering and realization of a broad family of two-dimensional phase singularity sheets and transverse polarization singularity sheets, opening up new aspects of light-matter interaction. Optical phase singularities are zeros of a scalar light field. The most systematically studied class of singular fields is vortices: beams with helical wavefronts and a linear (1D) singularity along the optical axis. Beyond these common and stable 1D topologies, we show that a broader family of zero-dimensional (point) and two-dimensional (sheet) singularities can be engineered. We realize sheet singularities by maximizing the field phase gradient at the desired positions. These sheets, owning to their precise alignment requirements, would otherwise only be observed in rare scenarios with high symmetry. Furthermore, by applying an analogous procedure to the full vectorial electric field, we can engineer paraxial transverse polarization singularity sheets. As validation, we experimentally realize phase and polarization singularity sheets with heart-shaped cross-sections using metasurfaces. Singularity engineering of the dark enables new degrees of freedom for light-matter interaction and can inspire similar field topologies beyond optics, from electron beams to acoustics.